(untitled) (Journal of Bio-Science, 2015)
Context: Neonatal sepsis is one of the most important causes of morbidity and mortality and C-reactive protein (CRP) an excellent biomarker has significant diagnostic and prognostic value for the treatment of septicemia patient. Objectives: To isolate and identify viable pathogens from blood culture and their antibiogram and to correlate CRP levels with septicemic child. Materials and Methods: A total of 273 cases among which 233 were clinically suspected septicemia cases and 40 were healthy controls in age group 0 day to 15 years were selected from United Hospital Ltd., Dhaka Bangladesh. Blood culture was analyzed by the instrument BACTEC 9120 series. CRP was measured from blood serum by the auto biochemical analyzer OLYMPUS AU 640 followed by immuno-turbidimetric method. The organisms were isolated by inoculation on blood agar and MacConkey agar media. Identification of the organisms was done by colony morphology, gram staining and biochemical tests. Sensitivity of isolates was done against antimicrobial agents by disc diffusing method. Results: Blood samples in total 233 cases of suspected septicemia in children were studied between the ages of 0 day to 15 years. Culture proven septicemia 39 (16.74%), probable septicemia 136 (58.37%) and nonsepticemic febrile patients 58 (24.90%) were found. The highest rate of blood culture positivity found among 5-10 yrs. age group (25.64%). Salmonella typhi (41.03%) was the most common infective agent. The rate of blood culture positivity was significantly higher (p<0.001) among patients without antimicrobial therapy (23.74%) than those in patients with antimicrobial therapy (6.38%). S. typhi were 75% sensitive to Ceftriaxone while azithromycin showed high rate resistance (85.71%). E. coli and Klebsiella pneumoniae were highly sensitive (100%) to imipenem but E. coli resistant (100%) to amikacin, amoxyclavonic acid ciprofloxacin, gentamicin, Cefepime and netilmicin. Resistant (100%) to gentamicin was observed from K. pneumoniae. Mean CRP values (mg/l) of blood culture proven septicemia group, probable septicemia group, non-septicemic febrile group and control group were 70.42, 34.05, 3.08 and 0.98 respectively. Both proven septicemia and suspected septicemia cases showed CRP concentration above the cut-off value (>6 mg/l) and p value significant (p<0.001). Statistically significant difference (p<0.001) was found when mean CRP level of proven septicemia group, probable septicemia group and non-septicemic febrile group each compared with control group. CRP concentration were significantly (p < 0.001) different among three study group. Conclusion: Most of the gram negative bacteria isolated from blood culture showed resistance to commonly used antibiotics. The predominant infective isolate was Salmonella typhi. In this study, CRP level is high (cut-off value 6 mg/l) both in proven and probable septicemia group. CRP may have a good biomarker tools in diagnostic and prognostic value. Investigation of blood culture should be done before antimicrobial therapy, DOI: http://dx.doi.org/10.3329/jbs.v21i0.22524 J. bio-sci. 21: 99-108, 2013